Algorithmic Bias in Artificial Intelligence as A Threat to The Right to Equality - Bagus Gede Ari Rama; Kadek Julia Mahadewi; Dewa Krisna Prasada (Inovasi Pratama Internasional. Ltd, 2026)
its potential to generate digital discrimination that undermines the principle of equality before the law in Indonesia. While AI is widely adopted to enhance data-driven decision-making across various sectors, its outputs are not inherently neutral, as they are shaped by training data and algorithmic design. This condition raises concerns regarding unfair treatment of individuals or groups, which may conflict with constitutional guarantees of equality and non-discrimination under the 1945 Constitution of the Republic of Indonesia and Law No. 39 of 1999 on Human Rights. Using a normative legal research method with statutory and conceptual approaches, this study analyzes relevant legal frameworks governing AI and human rights protection in Indonesia. The findings show that existing regulations, including provisions on electronic system governance and personal data protection, remain general and insufficient to address the complexity of algorithmic bias. Accordingly, this study argues for strengthening the legal framework through the adoption of algorithmic transparency requirements, mandatory bias testing in AI development, and the establishment of independent auditing mechanisms. These measures are necessary to ensure that AI systems operate fairly, accountably, and in alignment with human rights principles, particularly the protection of equality before the law.